Ontology Engineering 12th International Experiences and Directions Workshop on OWL, OWLED 2015, co-located with ISWC 2015, Bethlehem, PA, USA, October 9-10, 2015, Revised Selected Papers - Tamma, Valentina; Dragoni, Mauro; Gonçalves, Rafael; Ławrynowicz, Agnieszka (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the thoroughly refereed post-workshop proceedings of the 12th OWL: Experiences and Directions Workshop, OWLED 2015, held in Bethlehem, PA, USA, in October 2015, co-located with ISWC 2015, the International Semantic Web Conference. The 18 revised papers presented were carefully reviewed and selected from 35 initial submissions. Bridging the gap between ontology engineering practices and software engineering, the papers describe reuse methods employed throughout the ontology development cycle; modeling / terminological decisions, alignment and comparison between ontologies, how ontologies are stored, versioned, distributed, and consumed over the Web.